2017
DOI: 10.1155/2017/3104180
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of the Association between Polymorphisms in the Fibrinogen Alpha Chain Gene and Schizophrenia

Abstract: Our previous studies using the mass spectrum analysis provided evidence that fibrinopeptide A (FPA) could be a potential biomarker for schizophrenia diagnosis. We sought further to demonstrate that variants in the fibrinogen alpha chain gene (FGA) coded FPA might confer vulnerability to schizophrenia. 1,145 patients with schizophrenia and 1,016 healthy volunteers from the Han population in Northeast China were recruited. The association of three tag single nucleotide polymorphisms (SNPs) (rs2070011 in the 5′UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Gender-specific associations between variants of CHGB and SCZ have been revealed in a Korean population by Shin et al [15]. Conversely, a case-control study indicated that there was no significant association between SNPs of FGA and SCZ [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Gender-specific associations between variants of CHGB and SCZ have been revealed in a Korean population by Shin et al [15]. Conversely, a case-control study indicated that there was no significant association between SNPs of FGA and SCZ [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Our group also studied the association between the fibrinogen alpha chain gene polymorphisms and schizophrenia [11]. Another study also further to demonstrate that relationship between polymorphisms in the fibrinogen alpha chain Gene(FGA) and Schizophrenia [5].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinopeptide A (FPA) is a product of proteolysis by thrombin of fibrinogen [4]. Now some previous studies using the mass spectrum analysis to prove that fibrinopeptide A (FPA) could be a potential biomarker for schizophrenia diagnosis [5]. MicroRNAs (miRNAs) are single-stranded RNA molecules, consisting of 21-23 nucleotides, which has the function of regulation [6].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 445 SCZ patients were recruited from the Sixth Hospital of Changchun City and Siping Psychiatric Hospital. At least two independent experienced psychiatrists diagnosed the patients according to the tenth edition of International Classification of Diseases diagnostic criteria (ICD-10) [12]. Birthdate- and gender- matched control subjects were recruited from the Changchun Municipal Center for Disease Control and Prevention, and 515 healthy controls were free from mental illness.…”
Section: Methodsmentioning
confidence: 99%